Advances and limitations of semi-elastic pneumatic cuffs in blood flow restriction training: a narrative review - Stray-Gundersen, Sten; Stampley, James (Frontiers in Physiology, 2025)
Semi-elastic pneumatic (SEP) blood flow restriction (BFR) cuffs, such as the original KAATSU and the B Strong/B3 cuffs, have gained popularity as practical, user-friendly tools for low-load BFR exercise. However, their efficacy and optimal use remain somewhat debated, especially compared to rigid tourniquet-style cuffs that prescribe individualized arterial occlusion pressures (AOPs). This narrative review synthesizes the literature on SEP BFR devices with a focus on B Strong/B3 to clarify their acute and chronic effects and address unique methodological considerations. We first define SEP BFR cuffs and distinguish them from rigid AOP-calibrated cuffs, then summarize the acute and chronic physiological and perceptual responses and adaptations to resistance and aerobic exercise. Acutely, SEP BFR cuffs elicit pronounced local metabolic stress and fatigue. Longitudinally, SEP BFR training leads to significant improvements in muscle size, strength, and endurance. SEP BFR cuffs may offer practical advantages in safety and accessibility to a wide range of users by using a design that inherently limits the risk of arterial occlusion. We also discuss practical considerations for SEP BFR, propose alternative internal load monitoring such as near-infrared spectroscopy, and emphasize that the degree of fatigue and effort are primary hallmarks of an effective BFR training session. Finally, we propose future directions for research along with considerations on how to optimally apply and study SEP BFR. While SEP BFR cuffs are designed to not fully occlude arterial flow—thereby limiting their capacity for AOP standardization—they offer a pneumatically-controlled approach capable of delivering a safe and effective BFR training stimulus. Given their growing use in the field, researchers should not dismiss SEP BFR devices; instead, they should be systemically investigated and undergo direct comparisons with rigid AOP-based devices. Such research will help refine guidelines and broaden our understanding of how both SEP and AOP-calibrated BFR can be optimally applied.